2015
DOI: 10.1021/acs.inorgchem.5b01242
|View full text |Cite
|
Sign up to set email alerts
|

Two Dihydroxo-Bridged Plutonium(IV) Nitrate Dimers and Their Relevance to Trends in Tetravalent Ion Hydrolysis and Condensation

Abstract: We report the room temperature synthesis and structural characterization of a μ2-hydroxo-bridged Pu(IV) dimer obtained from an acidic nitric acid solution. The discrete Pu2(OH)2(NO3)6(H2O)4 moiety crystallized with two distinct crystal structures, [Pu2(OH)2(NO3)6(H2O)4]2·11H2O (1) and Pu2(OH)2(NO3)6(H2O)4·2H2O (2), which differ primarily in the number of incorporated water molecules. High-energy X-ray scattering (HEXS) data obtained from the mother liquor showed evidence of a correlation at 3.7(1) Å but only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The coordination sphere of each Pu IV ion is completed by two chloride ions and three bidentate nitrate ligands, which results in a distorted capped square antiprismatic coordination geometry (Figure 1B). One of the nitrate groups is perpendicular to the others, as has been observed for the bis(ammonium) hexanitratoplutonium(IV) synthesized by Spirlet et al [13] and the dihydroxo-bridged Pu IV nitrate dimers synthesized by Knope et al [9] However, unlike these previously reported structures, the bidentate nitrate groups at the top and bottom of The observed Pu-O nitrate and Pu-Cl bond distances are consistent with those previously reported for Pu IV . [4,7,9,13,14] Pu-O nitrate distances range from 2.477(2) to 2.577(4) Å with an average distance Bond valence calculations [26] were used to confirm the structure refinement (Table S7).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The coordination sphere of each Pu IV ion is completed by two chloride ions and three bidentate nitrate ligands, which results in a distorted capped square antiprismatic coordination geometry (Figure 1B). One of the nitrate groups is perpendicular to the others, as has been observed for the bis(ammonium) hexanitratoplutonium(IV) synthesized by Spirlet et al [13] and the dihydroxo-bridged Pu IV nitrate dimers synthesized by Knope et al [9] However, unlike these previously reported structures, the bidentate nitrate groups at the top and bottom of The observed Pu-O nitrate and Pu-Cl bond distances are consistent with those previously reported for Pu IV . [4,7,9,13,14] Pu-O nitrate distances range from 2.477(2) to 2.577(4) Å with an average distance Bond valence calculations [26] were used to confirm the structure refinement (Table S7).…”
Section: Resultssupporting
confidence: 89%
“…Pu IV metal centers, [4][5][6][7][8] though dihydroxo-bridged species have also been reported. [9] Dimeric complexes connected by a single μ 2 -oxo bridge gained a lot of attention in the late 1990s. [10] The primary focus was on understanding the the mixing of d-orbitals from the metal centers with the p-orbitals of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…For Ce and Pu, predominantly oxobridged species have been conclusively isolated. 63,72 However, after the discovery of hydroxo/oxo-bridged hexanuclear complexes for Pu(IV) and Ce(IV), [M 6 (μ 3 -O) 4 (μ 3 -OH) 4 ] 12+ (M = Pu, Ce) 73,74 and two dihydroxo-bridged Pu(IV) dimers, 75 it became clear that a simple hard and soft acid-base concept is not sufficient to predict the hydrolysis chemistry of these metal ions. The real mechanism of Pu hydrolysis appears to be much more complicated than simple olation or oxolation.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its diversity as well as its technological importance in the nuclear industry, the polymer and cluster chemistry of actinides (An) has been flourishing since the last decade. [1][2][3][4][5] In particular, the poly-oxo/hydroxo polymer and cluster complexes of tetravalent actinides (An(IV)) have received considerable attention, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] as the formation of these complexes stems primarily from their hydrolysis [21][22][23][24] and, hence, it would have significant implications for the natural and engineered aqueous systems associated with the nuclear industry. 25 The largest poly-oxo An(IV) cluster reported thus far is the {An 38 } complex, consisting of 38 An(IV) centres bridged by 56 oxygens.…”
mentioning
confidence: 99%
“…Given this construction manner, it is reasonable to infer that the formation of the primary {An 14 } core is followed by the attachment of the {An 4 } subunits to the surface of the cubic {An 14 } core. Owing to their strong olation/oxolation tendency, 31 An(IV) can form a variety of oligomer species 2 including soluble m 2 -hydroxo-bridged dinuclear species, 7,17,32 which could further evolve into hexanuclear species via hydrolysis. 6,10,11,14 A similar evolution of such oligomer species was also observed for Ce(IV), 33,34 a chemical analogue of An(IV).…”
mentioning
confidence: 99%